2015
DOI: 10.3389/fpsyg.2015.01756
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive Aggression and Adverse Childhood Experiences Shape Violent Behavior in Females Formerly Associated with Combat

Abstract: This study investigated the impact of violent experiences during childhood, posttraumatic stress disorder (PTSD) and appetitive aggression on everyday violent behavior in Burundian females with varying participation in war. Moreover, group differences in trauma-related and aggression variables were expected. Appetitive aggression describes the perception of violence perpetration as fascinating and appealing and is a common phenomenon in former combatants. Semi-structured interviews were conducted with 158 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 60 publications
3
24
0
Order By: Relevance
“…Our study results suggest that among the LRA abductees, individuals with combat experience showed higher levels of appetitive aggression than the ones without combat experience. This confirms the findings of a previous study with women formerly associated with combat in Burundi (Augsburger et al, 2015), however, in our study, we also included men. Interestingly, we could not detect any sex differences in our analysis for appetitive aggression.…”
Section: Appetitive Aggressionsupporting
confidence: 91%
“…Our study results suggest that among the LRA abductees, individuals with combat experience showed higher levels of appetitive aggression than the ones without combat experience. This confirms the findings of a previous study with women formerly associated with combat in Burundi (Augsburger et al, 2015), however, in our study, we also included men. Interestingly, we could not detect any sex differences in our analysis for appetitive aggression.…”
Section: Appetitive Aggressionsupporting
confidence: 91%
“…However, once adults become fighters, the same level of substantial appetitive aggression can be seen in both males and females ( 47 ). While the relationship between violence exposure and mental health per se may be similar in male and female samples, recent investigations have suggested distinct trajectories to aggression for female (ex)combatants, e.g., in interaction with childhood adversities ( 20 ). Separate studies for male and female survivors of combat are therefore required to understand the needs of these individuals and successfully mitigate the consequences of violence at the individual and societal levels.…”
Section: Introductionmentioning
confidence: 99%
“…While initially the attraction to violence was considered a potentially predominantly male phenomenon (Nell, 2006; Elbert et al, 2010), recent studies have revealed the occurrence of similar levels of appetitive aggression in both sexes involved in post-conflict regions (Augsburger et al, 2015; Meyer-Parlapanis et al, 2016). Appetitive aggression is likely to contribute to an elevated risk of rejoining an armed force after demobilization or a gang after a prison sentence (Maedl et al, 2010; Sommer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%